11/22/63 : a novel - King, Stephen (New York : Scribner, 2011)
On November 22, 1963, three shots rang out in Dallas, President Kennedy died, and the world changed. What if you could change it back? The author's new novel is about a man who travels back in time to prevent the JFK assassination. In this novel that is a tribute to a simpler era, he sweeps readers back in time to another moment, a real life moment, when everything went wrong: the JFK assassination. And he introduces readers to a character who has the power to change the course of history. Jake Epping is a thirty-five-year-old high school English teacher in Lisbon Falls, Maine, who makes extra money teaching adults in the GED program. He receives an essay from one of the students, a gruesome, harrowing first person story about the night fifty years ago when Harry Dunning's father came home and killed his mother, his sister, and his brother with a hammer. Harry escaped with a smashed leg, as evidenced by his crooked walk. Not much later, Jake's friend Al, who runs the local diner, divulges a secret: his storeroom is a portal to 1958. He enlists Jake on an insane, and insanely possible, mission to try to prevent the Kennedy assassination. So begins Jake's new life as George Amberson and his new world of Elvis and JFK, of big American cars and sock hops, of a troubled loner named Lee Harvey Oswald and a beautiful high school librarian named Sadie Dunhill, who becomes the love of Jake's life, a life that transgresses all the normal rules of time.
Watershed moment -- The janitor's father -- Living in the past -- Sadie and the general -- 11/22/63 -- The green card man.
Keywords: Time travel -- Fiction